2020
DOI: 10.1108/tqm-04-2020-0077
|View full text |Cite
|
Sign up to set email alerts
|

Adopting a digital transformation strategy to enhance business network commons regeneration: an explorative case study

Abstract: PurposeThis article aims to understand whether and how a digital transformation strategy (DTS) can strengthen the relationship between network organizations and the generation/regeneration of their business network commons (BNC). Further, it investigates the role of the DTS in managing the BNC, a critical source of business network success.Design/methodology/approachA two-year longitudinal case study of an Italian business network operating in the wine sector was conducted.FindingsThis study provides theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…Existing studies have found that the main driving factors of enterprise green innovation include environmental regulations [12], government subsidies [13], stakeholder requirements [14], and organizational characteristics [3]. However, there is a lack of research on how digital technology promotes green innovation and the sustainability of organizations and society [15]. Few studies have analyzed the role of digitalization in inducing green innovation from the perspective of enterprises as the subjects of digital transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have found that the main driving factors of enterprise green innovation include environmental regulations [12], government subsidies [13], stakeholder requirements [14], and organizational characteristics [3]. However, there is a lack of research on how digital technology promotes green innovation and the sustainability of organizations and society [15]. Few studies have analyzed the role of digitalization in inducing green innovation from the perspective of enterprises as the subjects of digital transformation.…”
Section: Introductionmentioning
confidence: 99%
“…First, we analyze the relationship between corporate digitalization and green innovation in the context of digital transformation, providing empirical evidence for the environmental benefits of corporate digitalization. We respond to Zoppelletto's [15] call for a detailed study on the relationship between digitalization and sustainable practices. Second, this study enriches the literature on corporate green innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings on the application of digital transformation have led to a clearer view of the role of digital transformation in enterprises. Regarding these, the study of Zoppelletto et al (2020) indicated that common business network common is mainly regenerated by digital resources; it comes from combining a digital transformation strategy and the business strategy of the network. In another study by Alvarenga et al, (2020) on digital transformation and knowledge management, the findings showed that the outstanding value of egovernment is the result of knowledge management quality in public sector organizations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital transformation is considered an essential element in enterprises (Onețiu, 2020), as it helps to take advantage of new technologies and optimize processes, innovate management systems, digitize products and services, and increase customer experience. Many helpful studies have significantly showed that the important role of digital transformation, such as the study by Zoppelletto et al (2020) which showed the combination of digital transformation and business strategy, and the results reported by Alvarenga et al, (2020) who demonstrated the considerable relationship between digital transformation and knowledge management in electronic government. In addition, high technology, such as digital technology, plays a key role in the decision to undertake digital transformation in any company in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Data-driven SCs enhance the SCs process and explore many digital technologies to enhance their performance and survive in the market (Chavez et al, 2017;Babatunde, 2020;Brunetti et al, 2020). Many digital technologies are available, such as predictive analytics, robotics, and IoT sensors, to smooth the process (Nica, 2019;Zoppelletto et al, 2020). Quality management (QM) is an essential aspect of SC management.…”
Section: Introductionmentioning
confidence: 99%